Sikap Masyarakat Kampus (Mahasiswa dan Dosen) Tentang Kebersihan Lingkungan Kampus Uin Sumatera Utara - N Neliwati (Jurnal Penelitian Medan Agama, 2018)
This study aims to find out: First, the attitudes of lecturers and students towards the cleanliness of the sidewalks and courtyards around the UIN campus of North Sumatra. Second, the attitude of lecturers and students to the cleanliness of toilets (bathrooms) at UIN North Sumatra. Third, the attitude of lecturers and students to the cleanliness of classrooms during the lecture process at UIN North Sumatra. This research was carried out using a qualitative approach. Data collection in this study is using observation, interviews and document review. The subjects of this study were lecturers and students of UIN North Sumatra who were taken through a purposive sampling technique. The instrument of data collection uses observation, interview, documentation techniques. The steps of data analysis are: Inductive analysis and Interim analysis. Conclusions obtained by the attitudes of lecturers and students about the cleanliness of the sidewalks and courtyards around the UIN SU campus, first, the uncomfortable attitude was shown in relation to the condition of the campus gate area which was less orderly and comfortable. Second, the happy attitude shown by the lecturers is that the greening program on campus adds to the calm and beautiful atmosphere.